2021
DOI: 10.3390/agronomy11010084
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Comparison of Ultrasound and Microwave-Assisted Extraction of Phenolic Compounds from Cotton-Lavender (Santolina chamaecyparissus L.)

Abstract: The interest in natural phenolic compounds has increased because of their attractive use especially as antioxidant and antimicrobial agents in foods. The large content in phenolic compounds of interest in Santolina chamaecyparissus L. (S. chamaecyparissus) makes this plant a target source that is worthy of note. In this work, new extraction technologies comprising ultrasound (UAE) and microwave (MAE) assisted extraction of the phenolic compounds in S. chamaecyparissus have been developed, optimized, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…While for the intermediate precision study, 4 extractions were performed on each one of three con- As it can be observed, the maximum amount of anthocyanins was extracted when the extraction time was 15 min, with a noticeable difference in relation to the 5 min extractions and no significant differences with regard to any other of the extraction times. This fact is in agreement with the extraction time required for the extraction of anthocyanins from other matrices [19,35,36]. Moreover, no decreasing trend in anthocyanins recoveries was observed when longer extraction times (over 15 min) were applied, which suggests that no anthocyanin degradation took place under such time conditions [50].…”
Section: Precision Studysupporting
confidence: 84%
See 2 more Smart Citations
“…While for the intermediate precision study, 4 extractions were performed on each one of three con- As it can be observed, the maximum amount of anthocyanins was extracted when the extraction time was 15 min, with a noticeable difference in relation to the 5 min extractions and no significant differences with regard to any other of the extraction times. This fact is in agreement with the extraction time required for the extraction of anthocyanins from other matrices [19,35,36]. Moreover, no decreasing trend in anthocyanins recoveries was observed when longer extraction times (over 15 min) were applied, which suggests that no anthocyanin degradation took place under such time conditions [50].…”
Section: Precision Studysupporting
confidence: 84%
“…Similarly, the temperature should not be above 70 • C because the solvent would start boiling and this would affect the final recovery. Some authors have observed that percentages of methanol near 70% were more optimal for the extraction of anthocyanins, especially from plant materials [19,35,49]. Finally, higher levels of methanol in the solvent were assayed while the rest of optimal extraction conditions according to the BBD were applied, i.e., 70 • C, 20 mL of solvent per 0.5 g of sample and pH = 5.…”
Section: Optimization Of the Uae Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvent-to-material ratio was considered to be one of the most important factors affecting the extraction yields of phenolic compounds [ 20 , 21 ]. A larger ratio of solvent-to-material was conducive to the rapid release of the intracellular substances and enhanced extraction yield [ 22 ]. Nevertheless, it was also found that a much large ratio of solvent-to-material would lead to a decline in the recovery efficiency [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to these non-conventional methods, the time required for a substantial extraction of the compounds of interest was reduced to just a few minutes (2-10 min). Aurach et al [5] used both ultrasound-assisted extraction (UAE) and microwave-assisted extraction (MAE) for the extraction of the phenolic compounds that are found in Cotton-Lavender (Santolina chamaecyparissus L.). The largest phenolic compounds' extraction yields from this matrix were achieved when MAE was employed.…”
mentioning
confidence: 99%